Integrativnošću (bio)etike do nove ekonomije - Donev, Dejan (Naučnoistraživački institut ”IBN SINA” Sarajevo, 2011)
To came to the wanted (bio)ethicsasing of the economy-life, those that manage must have and valuable system which axiology will be (bioethical) certain, but in the same time must have and a system which will be unclosed, evolutionary by its nature. This means that the generally wanted ethical values in managing must become, in the same time, and a norm in the behavior and working in any kind of managing. Becoming that, the change of the previous politics on the economies will be possible: from the directiveness to self and own interests toward to social responsibility and parthership. This means that their working will be subordinate to the need of the construction of a new global economy. But, global economy which won’t be grounded on the need of conquering new markets for old technologies, but to the conscience of the need of ethical and ecological preserved and justified development on the society as well as on the mankind generally. This will lead to that toward which, obviously, the whole world is aimed in the moment - global real democratized civil society aware for it’s own responsibility from irrational spending of the resource and the need of creating a conditions for survival of the variety - growing up to the general bioethical conscience in every human. The up grow of the economy to this kind of conscience is realized in the moment when, as a basic value in any thinking and evaluating of the management and managers, the basic point will be the bioethical conscience. So we’ll attain to life as an indisputable ethical value by it self and for it self, it’s protection and advancing. In this way and only in this way, we’ll get to that from which we started - return to ourself as a human, return ourself as a Man/Human, which, in the birth moment in its genetic code and recalling, will have Bioethics as a base for living.
Through integrativity of (bio)ethics (up) to a new economy
Keywords: fear, ethics, bioethics, management, global economy